Withaferin A-induced apoptosis in human breast cancer cells is mediated by reactive oxygen species. - Eun-Ryeong Hahm; Michelle B Moura; Eric E Kelley; Bennett Van Houten; Sruti Shiva; Shivendra V Singh (PLoS ONE)
Withaferin A (WA), a promising anticancer constituent of Ayurvedic medicinal plant Withania somnifera, inhibits growth of MDA-MB-231 and MCF-7 human breast cancer cells in culture and MDA-MB-231 xenografts in vivo in association with apoptosis induction, but the mechanism of cell death is not fully understood. We now demonstrate, for the first time, that WA-induced apoptosis is mediated by reactive oxygen species (ROS) production due to inhibition of mitochondrial respiration. WA treatment caused ROS production in MDA-MB-231 and MCF-7 cells, but not in a normal human mammary epithelial cell line (HMEC). The HMEC was also resistant to WA-induced apoptosis. WA-mediated ROS production as well as apoptotic histone-associated DNA fragment release into the cytosol was significantly attenuated by ectopic expression of Cu,Zn-superoxide dismutase in both MDA-MB-231 and MCF-7 cells. ROS production resulting from WA exposure was accompanied by inhibition of oxidative phosphorylation and inhibition of complex III activity. Mitochondrial DNA-deficient Rho-0 variants of MDA-MB-231 and MCF-7 cells were resistant to WA-induced ROS production, collapse of mitochondrial membrane potential, and apoptosis compared with respective wild-type cells. WA treatment resulted in activation of Bax and Bak in MDA-MB-231 and MCF-7 cells, and SV40 immortalized embryonic fibroblasts derived from Bax and Bak double knockout mouse were significantly more resistant to WA-induced apoptosis compared with fibroblasts derived from wild-type mouse. In conclusion, the present study provides novel insight into the molecular circuitry of WA-induced apoptosis involving ROS production and activation of Bax/Bak.